Visual Interpretation of Cultural Symbols of Shandong Folk Shoe Embroidery Pattern Paper Cutting - YueTong, Guo; Mohamed Salim, Neesa Ameera (Journal of Neonatal Surgery, 2025)
This study investigates the cultural symbolism embedded in Shandong Folk Shoe Embroidery Pattern Paper Cutting, with a focus on how these visual forms convey shared cultural values and collective identity. The research seeks to identify key cultural symbols that represent the transmissibility of common cultural beliefs and to examine how semiotic methods can be used to interpret these symbols. Drawing upon Ferdinand de Saussure’s semiotic concepts of “reference” and “denotation,” this study adopts a qualitative research design to analyze selected examples of folk paper cutting. The findings reveal that recurring motifs—such as butterflies, lotuses, bats, and magpies—serve as visual narratives symbolizing values like fortune, prosperity, longevity, and happiness. These symbols not only fulfill decorative purposes but also embody emotional resonance and social meaning, reflecting the aesthetic ideals and spiritual aspirations of local communities. The study concludes that this form of paper cutting integrates realism and symbolism, functioning as a medium of cultural expression and emotional articulation. Ultimately, this research offers insight into how traditional Chinese folk art operates as a vehicle for cultural transmission and emphasizes its relevance in contemporary efforts toward the preservation and revitalization of intangible heritage.